2009
DOI: 10.1016/j.ijpara.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Host associations and evolutionary relationships of avian blood parasites from West Africa

Abstract: The host specificity of blood parasites recovered from a survey of 527 birds in Cameroon and Gabon was examined at several levels within an evolutionary framework. Unique mitochondrial lineages of Haemoproteus were recovered from an average of 1.3 host species (maximum = 3) and 1.2 host families (maximum = 3) while lineages of Plasmodium were recovered from an average of 2.5 species (maximum = 27) and 1.6 families (maximum = 9). Averaged within genera, lineages of both Plasmodium and Haemoproteus were constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 43 publications
(60 reference statements)
8
130
1
Order By: Relevance
“…Traditionally, subtle morphological characters were used to distinguish taxa [25]. However, recent studies have demonstrated substantial genetic diversity within some morphospecies, and have raised the possibility of cryptic species in this system [31,[51][52][53]. However, the status of most haemosporidian parasites as biological species remains untested.…”
Section: (C) Resolving Parasite -Bird and Parasite-mosquito Relationsmentioning
confidence: 99%
“…Traditionally, subtle morphological characters were used to distinguish taxa [25]. However, recent studies have demonstrated substantial genetic diversity within some morphospecies, and have raised the possibility of cryptic species in this system [31,[51][52][53]. However, the status of most haemosporidian parasites as biological species remains untested.…”
Section: (C) Resolving Parasite -Bird and Parasite-mosquito Relationsmentioning
confidence: 99%
“…Recent surveys of blood parasites in vertebrate wildlife populations, using PCR to screen hosts for infections and DNA sequencing to identify parasite lineages, have revealed a rich diversity of hemosporidian parasites (3)(4)(5)(6), possibly comparable to the number of hosts surveyed (7,8). It is important to reevaluate our interpretation of hemosporidian evolution as we expand sampling, to provide insight into shifts among hosts and vectors-often implicated in emerging infectious diseases-and to interpret the evolution of malaria parasite life cycles.…”
mentioning
confidence: 99%
“…For example, one study showed marked and complex associations between avian malaria infections and landscape on a local scale, within a single population of birds (Wood et al, 2007). There has been extensive work conducted to determine the prevalence and diversity of these parasites in rainforest birds in WestCentral Africa (Beadell et al, 2009;Sehgal et al, 2005;Waldenström et al, 2002). This region of Africa is highly relevant to the investigation of effects of habitat modification due to continued high rates of deforestation and forest fragmentation (FAO, 2009).…”
mentioning
confidence: 99%